Peningkatan Pengetahuan Wanita Usia Subur tentang Persiapan Kehamilan yang Sehat di Wilayah Kerja Puskesmas Dolo Kabupaten Sigi - Baiq Tsaniya Sakkarwa (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2026)
Pregnancy preparation is an important effort to improve maternal and infant health through physical, mental, social, and nutritional readiness before pregnancy. However, many women of childbearing age (WUS) still lack adequate knowledge regarding healthy pregnancy preparation. This community service activity aims to increase the knowledge of women of childbearing age regarding healthy pregnancy preparation through health education. The activity was carried out on June 18, 2026, at the Maku Village Health Post, Dolo Community Health Center Working Area, Sigi Regency, targeting 6 women of childbearing age. The methods used included interactive lectures, leaflet distribution, discussions, and questions and answers. Evaluation was conducted using pre-tests and post-tests to measure the increase in participants' knowledge. The evaluation results showed that the average knowledge score of participants increased from 81.7 in the pre-test to 100 in the post-test. This increase in knowledge was also evident in the participants' ability to re-explain the importance of pre-pregnancy health checks, folic acid consumption, fulfilling a balanced diet, controlling risk factors, and consulting with health workers before planning a pregnancy. This activity shows that health education is effective in increasing the knowledge of women of childbearing age regarding healthy pregnancy preparation. It is hoped that similar educational activities can be conducted on an ongoing basis to improve women's preparedness for pregnancy and thus support healthy mothers and babies.